Association of Serum Alkaline Phosphatase and Bone Mineral Density in Maintenance Hemodialysis Patients - Park, Jong Chan (Hemodial Int, 2010)
Recent studies indicate that serum alkaline phosphatase (AlkPhos), a surrogate of high turnover bone disease, is associated with coronary artery calcification and death risk in maintenance hemodialysis (MHD) patients. The association between AlkPhos and bone mineral density (BMD) is not well studied. We studied the association between AlkPhos and dual-energy X-ray absorptiometry-assessed BMD in a group of MHD patients in Southern California. In 154 MHD patients, aged 55.3 +/- 13.6 years, including 42% women, 38% Hispanics, 42% African Americans, and 55% diabetics, the mean serum AlkPhos was 121 +/- 63 U/L (median: 101, Q(25-75): 81-141); 36% had AlkPhos>/=120 U/L and 50% had a total T-score< or =-1. Whereas the total BMD did not correlate with age (r=0.01, P=0.99) or body mass index (r=0.10, P=0.22), it correlated negatively with AlkPhos (r=-0.25, P=0.002), including after multivariate adjustment (r=-0.24, P=0.003). The proportion of patients with a high coronary artery calcification score>400 was incrementally higher across worsening BMD tertiles (P trend=0.04). The BMD was significantly worse in MHD patients with serum AlkPhos> or =120 U/L compared with <120 U/L (1.01 +/- 0.016 vs. 1.08 +/- 0.013 g/cm(2), respectively, P<0.001). The multivariate adjusted odds ratio of AlkPhos> or =120 U/L for having a total T-score<-1.0 was 2.3 (1.1-4.8, P=0.037). Among routine clinical and biochemical markers, serum AlkPhos> or =120 U/L was a better predictor of total T-score< or =-1 in MHD patients. An association exists between higher serum AlkPhos and worse dual-energy X-ray absorptiometry-assessed BMD in MHD patients. Given these findings, studies are indicated to examine whether interventions that lower serum AlkPhos improve BMD in MHD patients..